PENINGKATAN KEMAMPUAN BAHASA EKSPRESIF ANAK MELALUI KEGIATAN SANDIWARA BONEKA PADA MATA DIKLAT PRAKTEK PEMBELAJARAN DI RAUDHATUL ATHFAL (RA) - Yayah Kusbudiyah (Balai Diklat Keagamaan Bandung, 2018)
Research in the field of teachers Raudhatul Athfal still very less, this discussion fills the shortage. This study aims to find out the teacher's understanding of improving the ability of the expressive language of children through puppet activities that are practiced in the eyes of the Training Practice of Thematic Substance Technical Training Raudhatul Athfal in 2018. Researchers use descriptive research type with a qualitative approach to reveal facts in the field what is obtained through active discussion, brainstorming, and classroom learning practices. As for the result of research that is through the activity of puppet show, the ability of expressive language of children can increase along with the teacher's understanding of language development as one of the development areas that must be achieved from the 6 areas of development contained in the Level of Achievement Level of Child Development as stated in Permendiknas no 137 and 146 of 2014 on the National Standard for Early Childhood Education and Curriculum 2013 Early Childhood EducationKey words: Expressive Speak, Puppet Show, Learning Practice